2013
DOI: 10.4142/jvs.2013.14.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conditioned media from human amniotic epithelial cells on corneal alkali injuries in rabbits

Abstract: This study was performed to evaluate the effects of conditioned media (CM) from human amniotic epithelial cells (HAECs) on the corneal wound healing process. Eighteen rabbits (36 eyes) were used and randomly assigned to three groups according treatment: CM from HAECs (group 1), vehicle alone (group 2), and saline (group 3). Corneal alkali injuries were induced with 1 N sodium hydroxide. Each reagent used for treatment evaluation was injected into the dorsal bulbar subconjunctiva and the area of the corneal epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Thus, some transplanted cells could attenuate myocardial infarction depending on their powerful secretory capacity [ 9 ]. Additionally, hAEC-CM induced the differentiation of human umbilical cord blood mesenchymal stem cells into dopaminergic neuron-like cells [ 10 ] and promoted corneal wound healing in rabbits [ 11 ]. In previous studies, we found that hAECs transplantation increased the fertility of POF/POI mice and restored ovarian function by inhibiting granulose cells apoptosis and alleviating inflammatory reaction in chemo-injured ovaries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some transplanted cells could attenuate myocardial infarction depending on their powerful secretory capacity [ 9 ]. Additionally, hAEC-CM induced the differentiation of human umbilical cord blood mesenchymal stem cells into dopaminergic neuron-like cells [ 10 ] and promoted corneal wound healing in rabbits [ 11 ]. In previous studies, we found that hAECs transplantation increased the fertility of POF/POI mice and restored ovarian function by inhibiting granulose cells apoptosis and alleviating inflammatory reaction in chemo-injured ovaries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found IGF (61) , EGF, bFGF, IL-6, and IL-8 (62) in AM-CM and observed an increased proliferation of human corneal epithelial cells when treated with such a CM. Kim et al demonstrated that the use of CM from human AM epithelial cells exerts positive effects on wound healing in an experimental rabbit model with a corneal alkaline injury (63) . These outcomes were considered as a potential alternative for non-surgical treatment in cases of corneal epithelial defects (61)(62)(63) .…”
Section: Therapeutic Use Of Gf/cytokines In Ocular Surface Diseasesmentioning
confidence: 99%
“…Kim et al demonstrated that the use of CM from human AM epithelial cells exerts positive effects on wound healing in an experimental rabbit model with a corneal alkaline injury (63) . These outcomes were considered as a potential alternative for non-surgical treatment in cases of corneal epithelial defects (61)(62)(63) .…”
Section: Therapeutic Use Of Gf/cytokines In Ocular Surface Diseasesmentioning
confidence: 99%
“…The experimental topical instillation of the secretome in ocular diseases has shown significant improvement in corneal wound healing, attenuating corneal inflammation by inhibition of the proinflammatory cytokines and infiltration of inflammatory cells [ 94 , 95 ]. In allergic conjunctivitis, anti-allergic effects were shown with a reduction of inflammatory cell conjunctival infiltration, inhibition of B cells, mast cells, and histamine functions, through a COX-2-dependent mechanism [ 96 ].…”
Section: Stem Cell Therapymentioning
confidence: 99%